IMPLEMENTASI MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Bobo, Petrus Seingo (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title: The Implementation of Think Pair Share Learning Models to Improve Student Learning Outcomes]. The purpose of this study was to improve the learning outcomes of Class VII Students of SMP Negeri 1 Loura, the subject of Linear One Variable Equation through the Think Pair Share (TPS) Learning model. This type of research is classroom action research that is reflective by taking certain actions in order to improve and enhance classroom learning practices in practice and professionally. The subjects of the research were VII grade students of SMP Negeri 1 Loura for the Academic Year 2017/2018, amounting to 43 people. The data collection tools used were: tests and observations. Data analysis techniques were obtained from the teacher, student activity data and test results. The indicator of the success of this class action research is said to be successful if it reaches classical completeness of 75% with the Minimum completeness Criteria (KKM) 70. The results obtained, in the first cycle test students who completed reached 62.79% and incomplete reached 37.21%. While the second cycle of students who completed tests reached 81.39% and 18.61% of incomplete completed. And the average results of observations in the first cycle for the first meeting is 2.25 and for the second meeting is 2.63, and the results of observations in the second cycle for the first meeting is 3.00 and for the second meeting is 3.25. Based on the results of the study it can be concluded that the implementation of the TPS learning model can improve student learning outcomes.